Effect of Acupressure on Primary Dysmenorrhea: Review of Experimental Studies - Aslı Karakuş Selçuk; Emre Yanikkerem (Medical Association of Pharmacopuncture Institute, 2021)
Primary dysmenorrhea is defined as cramping pain in the lower abdomen with no pelvic diseases, and it has a high prevalence in many countries. Acupressure is a widely used complementary treatment method for primary dysmenorrhea. This review examined experimental studies to determine the effects of acupressure on primary dysmenorrhea using the databases PubMed, Google Scholar, and CINAHL with the keywords "Acupressure" and "Dysmenorrhea". There were 2227 records in the databases, and 330 articles were published between 1989 and March 2020. Experimental studies in the English language were reviewed according to the PRISMA guidelines. This review included 28 published studies that were assessed using the Jadad score for quality. The studies were categorized as studies of acupressure at the LR3 point (n = 4), at the SP6 point (n = 9), at auricular points (n = 5), at multiple points (n = 8), and with devices (n = 2). Moreover, studies of self-acupressure (n = 9) were identified. The studies demonstrated that acupressure could reduce menstrual symptoms, the severity and duration of menstrual pain, distress, and anxiety. Furthermore, it helped improve the quality of life and well-being of patients and provide psychological support and self-care. Acupressure is an inexpensive, easy-to-apply, and non-pharmacological treatment and is useful for reducing primary dysmenorrhea, and women can apply this method anywhere by themselves. However, high-quality randomized controlled trials with larger samples are necessary to establish the evidence for acupressure as an effective intervention.